Characterization and Evaluation of a Novel Conserved Membrane Antigen P35 of Mycoplasma synoviae - Sun, Qianjin; Wei, Xiaona; Chen, Wei; Zhong, Qian; Yan, Zhuanqiang; Zhou, Qingfeng; Cao, Yongchang; Chen, Feng (Frontiers in Veterinary Science, 2022)
Mycoplasma synoviae (MS) is a major avian pathogen that causes respiratory damage, infectious synovitis, and arthritis in chickens and causes serious economic losses to the global poultry industry. Despite its significance, knowledge on pathogenicity and pathogenic mechanism of MS is lacking, especially regarding its antigens. Bioinformatic analysis showed that the known MS proteins are only the tip of the iceberg among many MS membrane proteins. In this study, we identified and expressed a novel MS membrane protein P35. Sequence similarity showed that P35 was conservative and commonly existed among MS strains. Membrane protein extraction and immunofluorescence assay confirmed that P35 was distributed on the surface of MS. The production of specific antibodies after immunization with recombinant protein rP35 suggested its immunogenicity. The antigenicity of P35 was evaluated from two aspects by using polyantiserum against MS and rP35. Furthermore, in assays to identify the immune peptides of P35, all successfully expressed truncated segments could react with positive polyantiserum of MS, suggesting that P35 had more than one immune peptide. In conclusion, our study successfully identified P35 as a conservative antigen of MS, which may act as a potential candidate for the future development of a vaccine against MS.